University of Ghana Housing Regulations - Public Affairs (University of Ghana, 2016)
According to current conditions of service for Senior Members and Entitled Staff, the University of Ghana shall provide accommodation to all Senior Members and to Senior Staff of the rank of at least Principal Administrative Assistant, or its equivalent. Attempts shall be made to accommodate Senior Members and Entitled Staff in the University's own houses. Where these are not readily available, the University shall provide rented premises in suitable areas outside the campus, at rates to be agreed upon by the University and the Landlords/ladies. The allocation of University houses to Senior Members and Entitled Staff is governed by regulations approved by the Academic Board and administered by the Housing Committee.
University of Ghana Special Reporter
University of Ghana Housing Regulations
Keywords: Report; Policy; University of Ghana; Housing Regulations